Negotiating Soundscape: Practice and Regulation of Adzan in Indonesia - Siti Aliyuna Pratisti (Journal of Indonesian Social Sciences and Humanities, 2020)
This article explores the historical context of practice and regulation of Adzan in Indonesia. As historical underpinnings, this article will follow a structural timeline of post-independence Indonesia to the current development of the state’s regulations of Adzan. To understand the social context of Adzan, Schafer’s conception of Soundmark and Hirschkind’s ethical soundscapes will be employed as theoretical framework to analyze how Indonesian (government and civil society) negotiates social tension caused by the use of loudspeaker in Indonesian mosques. Government regulations will be used as primary sources, while newspaper, journal and websites, provide additional information on the practice and regulations of Adzan in Indonesia. This article, however, will limit its study to the historical and social aspect of Adzan. Discussion on the theological aspect will not be covered by this article.